Mengintegrasikan Psikologi Islam dan Neurosains Perkembangan dalam Pendidikan Islam Anak Usia Dini: Pendekatan Holistik Berbasis Fitrah - Nurhayati; Juni Mahanis; Yuli Fatimah Warosari (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to examine the integration of Islamic psychology and developmental neuroscience in early childhood Islamic education through a holistic fitrah-based approach. A qualitative field research design was employed in Raudhatul Athfal institutions in Batam City, involving teachers, principals, and parents. Data were collected through observation, in-depth interviews, and documentation, and analyzed using an interactive model. The findings indicate that Islamic psychological principles are implemented primarily through value internalization and behavioral habituation rather than explicit theoretical instruction. Learning practices emphasize the balanced development of cognitive, emotional, social, and spiritual domains, reflecting a holistic approach aligned with children’s innate disposition (fitrah). These practices are consistent with neuroscience perspectives highlighting the importance of early experiences and environmental stimulation in shaping development. However, several challenges were identified, including limited conceptual understanding among educators, lack of interdisciplinary training, absence of standardized assessment tools, and variation across institutions. The study concludes that a more structured and theoretically grounded model is needed to strengthen the integration of Islamic psychology and developmental science in early childhood education.